Analisis Semiotika Pesan Motivasi Mencintai Diri Sendiri pada Lagu “Si Lemah” Karya RAN feat. Hindia - Fitria Nabillah Nabillah; Ferry Darmawan (UNISBA Press, 2023)
Abstract. Song is a communication tool that involves songwriters and listeners where songwriters can convey messages to listeners through mass communication. Songs can be effective learning tools if the messages in them are well conveyed. This study aims to analyze the text of motivational messages and the relationship between signs and motivation by using objects from the lyrics of the song